Chromosomal polymorphism in 12 populations of Mikania micrantha (Compositae) - Maffei, Eliane M.D.; Marin-Morales, M.A. [UNESP]; Ruas, P.M.; Ruas, C.F.; Matzenbacher, N.I. (Sociedade Brasileira de Genética, 1999)
Mikania micrantha é uma planta herbácea perene, da família Asteraceae, amplamente distribuída através de todo o continente americano. No Brasil, M. micrantha tem distribuição irrestrita, ocupando os mais variados ambientes, sem no entanto apresentar variação morfológica. Neste trabalho, usando o método de coloração de Feulgen e bandamento C, foram analisados os cromossomos mitóticos de 12 populações de M. micrantha, obtidos de diferentes localidades do Brasil. Citótipos numéricos e estruturais foram identificados, incluindo oito diplóides (2n = 36 e 42) e quatro tetraplóides (2n = 72). Os números cromossômicos de 2n = 36 e 2n = 42 são mostrados pela primeira vez para M. micrantha. Todos os cariótipos apresentaram o primeiro par de cromossomos com uma constrição secundária na região mediana do braço maior, seguindo o mesmo padrão observado em todas as espécies de Mikania já estudadas. A análise cromossômica revelou que todos os citótipos variam em algum aspecto. A origem desta variação é atribuída principalmente a ocorrência de inversões e deleção ou adição de fragmentos de DNA. Análise de banda C em três das 12 populações investigadas revelou polimorfismo na distribuição de heterocromatina. Cromossomos extranumerários, variando em número e morfologia, foram também identificados em seis citótipos de M. micrantha. O bandamento C mostrou que os cromossomos Bs apresentaram-se com o mesmo padrão heterocromático dos cromossomos do complemento normal, sugerindo uma possível origem a partir dos cromossomos A.

Mikania micrantha is a climbing perennial weed of the family Asteraceae, with a vast distribution from South America to south of the United States. This species is widely distributed throughout Brazil, where it shows little morphological variation. Mitotic chromosomes of 12 populations of M. micrantha derived from several Brazilian sites were studied using Feulgen staining and C-banding. The populations included eight diploid (2n = 36 and 42) and four tetraploid (2n = 72) cytotypes. Chromosome numbers of 2n = 36 and 2n = 42 are reported for the first time for M. micrantha. These populations had a secondary constriction in the middle of the larger arm of chromosome pair 1, following the same pattern described for all Mikania species analyzed so far. Numerical and structural variation of the chromosomes was quite common among the karyotypes and nearly all cytotypes differed from each other in some aspect. Most of the chromosomal differentiation may be attributed to inversions and addition or deletion of DNA fragments. C-banding, applied to three of the 12 populations, also revealed polymorphism in the distribution of heterochromatin. Additionally, one to 14 supernumerary or B-chromosomes were observed. The Bs were detected in six of the 12 populations and varied in size, number, and structure among karyotypes and also among cells of the same root meristem. The B chromosomes were also heterochromatic, showing a C-banding pattern similar to the A chromosomes, and suggesting that they may be derived from the chromosomes of the A complement.